METHODS OF QUANTITATIVE ANALYSIS IN CLINICAL LABORATORY DIAGNOSTICS (Modern education and development, 2025)
When conducting biochemical analyses in clinical diagnostic laboratories use methods of quantitative determination of components in biological fluids on the basis of modern advances in medical science and technology, providing high quality research, mechanisation and automation of laboratory work.